Challenges and Opportunities of Virtual Learning Factories in Comparison to Physical Learning Factories - Thomas , Kevin; Hoffmann , Stefanie; Winkler , Herwig (Management and Production Engineering Review, 2026)
Learning factories are widely used in engineering education to enable hands-on learning in realistic production environments. Traditionally, these learning environments have been implemented as physical factories, which require substantial financial, spatial, and personnel resources. Advances in digitalization and virtualization have led to increasing interest in virtual learning factories (VLF) as a potential alternative. This paper investigates whether VLF can be considered a viable alternative to physical learning factories (PLF) and identifies their key characteristics, advantages, limitations, opportunities, and risks. A systematic literature review was conducted using the Web of Science, EBSCOHost, and Google Scholar databases, resulting in a qualitative analysis of 44 relevant publications published between 2010 and 2023. The results show that VLF share core didactic principles with PLF, such as project-based learning in multi-stage production environments. Their main advantages include flexibility, scalability, reduced resource consumption, remote accessibility, and enhanced visualization of production processes. However, significant limitations remain, particularly regarding the lack of haptic feedback, high development effort, dependency on specialized personnel, and limited realism of simulated production resources. The study concludes that VLF cannot fully replace PLF but represent a complementary and resource-efficient extension, particularly for planning, analysis, and early-stage training. Future research should focus on standardized architectures, improved sensory immersion, and the integration of human-centered and organizational aspects.